Dental management before radiotherapy of the head and neck region: 4‐year single‐center experience - Lea Hoffmann; Sebastian N. Marschner; Tamara K. Kakoschke; Reinhard Hickel; Hisham Sabbagh; Uta C. Wölfle (Wiley, 2022)
Abstract Objective To review our experience with a standardized dental management approach in patients with planned radiotherapy of the head and neck region based on preradiation and follow‐up data. Material and Methods Records of patients who underwent radiotherapy between June 2016 and November 2020 were reviewed. Data on dental findings and therapeutic recommendations were extracted from a prospectively managed database. Hospital records were used to obtain follow‐up data. Results Two hundred eighty‐one patient records were identified. After the exclusion of 81 patients because of incomplete data, 200 patients were included in the study. Dental findings relevant to radiotherapy were found in 144 cases (72.0%). Teeth extractions were recommended in 112 (56.0%) patients. Follow‐up data were available for 172 (86.0%) patients (mean follow‐up: 16.8 ± 10.7 months). Radiodermatitis was the most frequently observed sequela of radiotherapy (42.4%), followed by dysphagia (38.4%) and stomatitis (36.6%). Osteoradionecrosis was observed in only 2.3% of the patients. Conclusion Dental findings relevant to planned radiotherapy were frequent and in many cases resulted in recommendations for teeth extraction. Based on our standardized dental management protocol, we observed low rates of late oral complications after radiotherapy of the head and neck region.